Golden Generation Preparation and Its Contribution to the Moderate Global Relations - Ünsal, Ali (Proceedings of International Conference on Da'wa and Communication, 2020)
The Golden Generation is the most beautiful fruit of human beings. The symbol of love and peace, which beautifies the life of the world, brings matter and meaning in balance, represents good morality, in short, it is the projection of the “insan-ı kamil” Muhammad pbuh and his companions in every century. The Golden Generation is an open-minded and compassionate generation that combines Islamic values with modernity, can integrate with the whole world. Within the framework of this article, we will try to examine what the “Golden Generation” concept used by M. Fethullah Gulen in the last 50 years includes, how they were raised, what they did, and especially what kind of its contribution they do to the moderate global relations. In doing so, we will include the testimony and reports of researchers, academics, scientists, clergymen, intellectuals, writers, and statesmen from different parts of the world to be objective.